Platform Crowdfunding Syariah: Paradigma Baru dalam Pembiayaan untuk Startup dan Usaha Kecil di Era Digital - Makki, Mustaqim; Suwardi, Suwardi (Journal of Economic and Business Law Review, 2024)
Sharia crowdfunding platforms have evolved as a new paradigm in financing in the digital age, especially for startups and small and medium-sized enterprises (SMEs). The platform offers a more ethical solution by adhering to sharia principles such as mudharabah (profit-sharing) and musharakah (partnership), allowing equitable sharing of risk and profit between investors and business managers. The use of modern technologies such as blockchain, smart contracts, and digital payments has strengthened efficiency, transparency, and security in these platforms. However, some of the main challenges in its implementation include low Islamic financial literacy, immature regulation, as well as limited technological infrastructure. This study aims to explore the potential of sharia crowdfunding as an inclusive financing solution for startups and SMEs, as well as identify the challenges and opportunities that exist in its operationalization. The results are expected to provide recommendations for the development of supportive regulation, increased financial literacy, and the development of adequate infrastructure to maximize the role of sharia crowdfunding in supporting inclusive and sustainable economic growth in the digital age.